Predator–prey interactions of terrestrial invertebrates are determined by predator body size and species identity. Issue 5 (21st March 2022) - Miller‐ter Kuile, Ana; Apigo, Austen; Bui, An; DiFiore, Bartholomew; Forbes, Elizabeth S.; Lee, Michelle; Orr, Devyn; Preston, Daniel L.; Behm, Rachel; Bogar, Taylor; Childress, Jasmine; Dirzo, Rodolfo; et al.
Abstract: Predator–prey interactions shape ecosystems and can help maintain biodiversity. However, for many of the earth's most biodiverse and abundant organisms, including terrestrial arthropods, these interactions are difficult or impossible to observe directly with traditional approaches. Based on previous theory, it is likely that predator–prey interactions for these organisms are shaped by a combination of predator traits, including body size and species‐specific hunting strategies. In this study, we combined diet DNA metabarcoding data of 173 individual invertebrate predators from nine species (a total of 305 individual predator–prey interactions) with an extensive community body size data set of a well‐described invertebrate community to explore how predator traits and identity shape interactions. We found that (1) mean size of prey families in the field usually scaled with predator size, with species‐specific variation to a general size‐scaling relationship (exceptions likely indicating scavenging or feeding on smaller life stages). We also found that (2) although predator hunting traits, including web and venom use, are thought to shape predator–prey interaction outcomes, predator identity more strongly influenced our indirect measure of the relative size of predators and prey (predator:prey size ratios) than either of these hunting traits. Our findings indicate that predator body size and species identity are important in shaping trophic interactions in invertebrate food webs and could help predict how anthropogenic biodiversity change will influence terrestrial invertebrates, the earth's most diverse animal taxonomic group.